Information history - an introduction : Exploring an emergent field - Weller, Toni (Chandos information professional series., 2008)
This is a pioneering introduction to the emergent field of information history. It explores how the contemporary values and concerns of our own information society have helped lead to a reconsideration of our history, and of what constitutes our historical understanding of information in the twenty-first century. In Information History, Toni Weller examines the historiography of information and asks how the key schools of thought have explored the concept in terms of its social, technological, economic and cultural understandings. Based on personal experiences, the author also proposes some practical applications of information history in research and university teaching, offering some suggestions as to how the field may develop based on its growth during the last decade.